Clinical researchHow can we decrease mortality in surgery units? - Piechota, Mariusz; Banach, Maciej; Jacoń, Anna; Rysz, Jacek (Archives of Medical Science, 2007)
Introduction: Factors affecting mortality of patients hospitalized in general surgery units are very differentiated. The authors analysed the factors affecting the mortality on three general surgery units in 3 different University Hospitals (UH) in Lodz, Poland. Material and methods: The study comprised 26,020 patients treated in these units from 01.01.2003 to 31.12.2006. The available statistical material was analysed. In the first stage the statistical data were analysed of the Provincial Centre of Public Health in Lodz. In the second stage the structure of the analysed units and the structure of the selected groups of diagnoses were compared. The third stage was focused on explaining the reasons of significantly lower mortality among patients hospitalised in surgical unit of UH No. 5. Results: The relative structure similarity indices of the hospitalized patients in general surgery units in the selected hospitals according to the basic disease (A00-A99; …; Z00-Z99) in the years 2003-2006 were respectively: UH No. 1/UH No. 2 – 0.511; UH No. 1/UH No. 5 – 0.549; UH No. 2/UH No. 5 – 0.637 and 0.418 together for UH No. 1/UH No. 2/UH No. 5. The mortality in group of patients with diagnosed C00-C97 was respectively: in UH No. 1 14.52%, in UH No. 2 6.21% and in UH No. 5 2.42% (UH No. 1/UH No. 5, p<0.001 and UH No. 2/UH No. 5, p<0.02). In the most numerous group (K00-K93) the mortality was respectively: in UH No. 1 1,30%, in UH No. 2 0.62% and in UH No. 5 0.10% (UH No. 1/UH No. 5, p<0.001 and UH No. 2/UH No. 5, p<0.03) (after appropriate modification of the structure and number of deaths). Conclusions: Change of the system of postoperative care consisting in: taking over postoperative care by physicians and anaesthesiological nurses, intensive monitoring of postoperative patients, immediate transfer of patients with life hazard to Intensive Care Unit, which was implemented in UH No. 5, significantly reduces the mortality in a surgical unit.